Hydrogen Diffusion Guided Design of Pt‐Based Alloys for Inhibition of Butadiene Over‐Hydrogenation. Issue 14 (17th July 2019) - Hu, Chaoquan; Sun, Jiahan; Wang, Dongjie; Peng, Mi; Shao, Mingyuan; Zhu, Qingshan; Ma, Ding
Abstract: The front cover artwork is provided by the groups of Dr. Chaoquan Hu, Prof. Qingshan Zhu (Institute of Process Engineering, Chinese Academy of Sciences), and Prof. Ding Ma (Peking University, P.R. China). The image shows the inhibition of C=C bond hydrogenation by increasing the barrier for H atom diffusion to the site, on which the H atom shares two Pt atoms with the C=C bond. Read the full text of the Article at 10.1002/cphc.201900380 . Abstract : "We have demonstrated a process to screen Pt‐based alloys for inhibition of butadiene over‐hydrogenation with a model comprising isolated single atoms embedded into Pt(111)…" This and more about the story behind the front cover can be found in the Article at 10.1002/cphc.201900380 .